2011
DOI: 10.4103/0974-1208.82360
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial regeneration using autologous adult stem cells followed by conception by in vitro fertilization in a patient of severe Asherman′s syndrome

Abstract: In a woman with severe Asherman's syndrome, curettage followed by placement of intrauterine contraceptive device (IUCD) (IUCD with cyclical hormonal therapy) was tried for 6 months, for development of the endometrium. When this failed, autologous stem cells were tried as an alternative therapy. From adult autologous stem cells isolated from patient's own bone marrow, endometrial angiogenic stem cells were separated using immunomagnetic isolation. These cells were placed in the endometrial cavity under ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(69 citation statements)
references
References 10 publications
1
63
0
5
Order By: Relevance
“…Recently, a case report showed that intrauterine administration of autologous BMSCs could repair the injured endometrium and result in subsequent pregnancy in a woman with severe IUAs, which was not responding to TCRA followed by the placement of IUD and cyclical hormonal therapy (Nagori et al 2011). Another study presented that autologous stem cell transplantation led to endometrial regeneration reflected by restoration of menstruation in five out of six patients with refractory Asherman's syndrome (Singh et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a case report showed that intrauterine administration of autologous BMSCs could repair the injured endometrium and result in subsequent pregnancy in a woman with severe IUAs, which was not responding to TCRA followed by the placement of IUD and cyclical hormonal therapy (Nagori et al 2011). Another study presented that autologous stem cell transplantation led to endometrial regeneration reflected by restoration of menstruation in five out of six patients with refractory Asherman's syndrome (Singh et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of biologics has been pursued to boost the regeneration process and/or minimize post-operative adhesions, including intrauterine infusion of autologous bone marrow-derived mesenchymal stem cells (BM-MSCs) [12], human amnion graft placement [13], or autologous peripheral blood CD133+ BM-MSC delivered into the uterine spiral arterioles by catheterization [14]. These have not been widely adopted likely due to the complexity of the techniques and conflicting outcomes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Так, в исследовании C. Nagori и соавт. [53] пациентке 33 лет с первичным бесплодием и синдромом Ашермана в полость матки введены аутологичные МSC (CD9 + , CD90 + , CD133 + ), полученные из костного мозга. После трансплантации и гормональной терапии отмечено увеличение толщины и васкуляризации эндометрия.…”
Section: перспективы клинического применения эндометриальных стволовыunclassified